2018
DOI: 10.1111/iwj.12845
|View full text |Cite
|
Sign up to set email alerts
|

Nicorandil‐induced ulcerations: a 10‐year observational study of all cases spontaneously reported to the French pharmacovigilance network

Abstract: Nicorandil-induced ulcers remain often poorly recognised, with a late diagnosis and an inadequate management. We aimed to provide a clinical overview of the 148 spontaneously reported cases of nicorandil-induced ulcers to the French pharmacovigilance network between 2005 and 2014 and to complete this picture with worldwide published cases over the same period. Spontaneously reported nicorandil-induced ulcers were mainly mucosal (oral and anal) with a previous trauma in 23·0% of patients, revealed by a severe c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 80 publications
0
13
0
Order By: Relevance
“…In 1997, the first reports appeared of gastrointestinal ulceration and fistulation in association with nicorandil use. 3,8,9 General consensus from these initial case reports and observational studies was that the adverse effects cannot be predicted. However, more recent data have shown that individuals with diverticular disease are at an increased risk of bowel perforation 10 and are seven times more likely to develop a fistula.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In 1997, the first reports appeared of gastrointestinal ulceration and fistulation in association with nicorandil use. 3,8,9 General consensus from these initial case reports and observational studies was that the adverse effects cannot be predicted. However, more recent data have shown that individuals with diverticular disease are at an increased risk of bowel perforation 10 and are seven times more likely to develop a fistula.…”
Section: Discussionmentioning
confidence: 99%
“…It is hypothesized that in these outpouchings, nicorandil's toxic metabolites accumulate causing epithelial proliferation and subsequent tissue ulceration. 8 Additionally, it has been postulated that nicorandil releases proinflammatory nitric oxide, which may also trigger the development of fistulas among sigmoidal diverticula. 3 The main clinical implication of our study is the potential for the use of a GRS to predict adverse side effects with nicorandil use.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients may present with ulcers, which are usually painful, in the mouth, around the anus, or on the cornea, skin, or genitalia 214151617. Those with ulcers in the bowel may present with gastrointestinal haemorrhage.…”
Section: How Do Patients With This Adverse Reaction Present?mentioning
confidence: 99%